DEM analysis of the effect of bond pattern on the load bearing capacity of barrel vaults under vertical loads. (14th May 2021) - Chen, Shipeng; Ferrante, Angela; Clementi, Francesco; Bagi, Katalin
Bond patterns influence responses of masonry barrel vaults to mechanical loads. In this research, the discrete element method (DEM) was applied to investigate how bond patterns affect the static load bearing capacity of barrel vaults under vertical loads. The two most widely-used bond patterns (transverse and longitudinal) were studied. Using a commercial DEM software, 3DEC, vaults with different angles of embrace were prepared according to both patterns, and then loaded in three alternative ways until failure. The failure loads were recorded, and compared for the two alternative patterns of each overall geometry. Two competing effects were found: 1) in transversal vaults the arches work nearly independently of each other which decreases the load resistance in comparison to longitudinal vaults; 2) larger size of the voussoirs along the arch direction increases the load bearing.